Beyers Naudé (1966–1977) Between Western ideals and black leadership - Wyngaard, Cobus van ca. 21. Jh. (2020)
This article examines public lectures of Beyers Naudé from 1966 until his banning in 1977, tracing on the one hand his critique on apartheid shortly before his engagement with black consciousness, and then his reception of black consciousness. Working from a 1967 lecture mostly ignored in literature to the present, Freedom in South Africa, onwards, the article illustrates how Naudé equates a particular normative understanding of Western emancipatory thought with the work of God in order to reject apartheid, and how Naudé employed an anti-communist rhetoric into his critique of apartheid. The second part of the article then turns to his reception of black consciousness, illustrating some of the limitations in his early interpretation of black consciousness, and concluding with his shifting perspective on where the voice of liberation and freedom will emerge from in South Africa.